Testing Adam-Gibbs relationship in tapped granular packings - Xinyu Ai; Houfei Yuan; Shuyang Zhang; Zhikun Zeng; Hanyu Li; Chengjie Xia; Yujie Wang (Communications Physics)
Abstract Disordered granular packings share many similarities with supercooled liquids, particularly in the rapid increase of structural relaxation time within a narrow range of temperature or packing fraction. However, it is unclear whether the dynamics of granular materials align with those of their corresponding thermal hard sphere liquids, and the specific influence of friction in a granular system remains largely unexplored. Here, we experimentally study the slow relaxation and the steady state of monodisperse granular sphere packings under vertical tapping using X-ray tomography. We first calculate the thermodynamic parameters including the effective temperature and configurational entropy under the Edwards’ ensemble of packings of granular spheres with varying friction, and measure their characteristic relaxation time during compaction. We then present a unified picture of the relaxation process in granular systems, in which a generalized Adam-Gibbs relationship is followed. These results clarify the close relationship between granular materials and the ideal frictionless hard sphere model.